The adjustment and analysis of dam monitoring networks - A. K., Abd. Majid; Kit Meng, Yip; Musa, Tajul A. (Fakulti Kejuruteraan & Sains Geoinformasi, Universiti Teknologi Malaysia., 1997)
Monitoring of dams is one of the classic topics for the application of geodesy to engineering. This research presents the results of the adjustment and analysis of a dam monitoring network that has been observed for the last ten years. The least squares adjustment technique has been used to carry out the 3-dimensional network adjustment. A subroutine called DETECT has been developed for the comparison of result from different epochs to compute displacement occurred in the monitoring process. Moreover, this subroutine is able to present the displacement in graphical form for a better interpretation. On the data acquisition technique, we have proposed that an Automated Theodolite Measuring System (ATMS) for the monitoring the dam structure and GPS surveying for backward control be implemented in the monitoring of a dam structure. It should be possible to transfer this concept with ease to different monitoring task as well.